Identifying and Measuring Technical Debt in Software Requirements: a supporting guide - Melo, Ana Carolina Candido De; Accioly, Nathália; Fagundes, Roberta; Santos, Wylliams (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2023: Anais do XIX Simpósio Brasileiro de Sistemas de Informação, 2023)
Context: Identification and measurement are the first steps in managing a Technical Debt (TD). They are essential to know the type of TD and estimate its impact on the software. Problem: However, in requirements engineering, these steps are little explored in academic research since the measurement is considered one of the most challenging phases. Solution: This work aims to develop a support guide to help software development professionals identify and measure the TD of requirements in their projects. IS Theory: This work was conceived under the aegis of the Customer Focus Theory. The requirements of TD management directly impact the quality of the product that will be delivered to the customer. Method: Initially, a systematic literature review was conducted, and a survey was applied with software development professionals allocated to different organizations. Additionally, the guide was developed and evaluated by four specialists through a focus group session. Summary of Results: Among the results, it became possible to present the existing strategies that help identify and measure the DT of requirements, in addition to tools and metrics that are used to automate the management process. Contributions and Impact in the IS area: After analyzing the results, it can be concluded that the guide is a resource that helps, especially professionals with a low level of knowledge in the area, obtain more information about TD. In addition, one of the contributions is investigating an interdisciplinary area, as TD involves social, technological, and organizational aspects.